A Study on Improving Dyeability of Polyester Fabric Using Lipase Enzyme - Kumar Jeyaraman Anandha; Senthil Kumar M. (AUTEX Research Journal, 2020)
Enzymatic hydrolysis on synthetic fibers enhances the hydrophilicity and solves the concerns regarding the environmental issues of textile industry. Lipase hydrolyses ester linkages in polyethylene terephthalate and produces polar hydroxyl and carboxylic groups. The study aims to identify and investigate the effect of enzyme treatment on weight loss and surface modification of polyester fabrics. Also the functional groups present before and after treatment and the effect of enzyme treatment on the improvement of dye uptake are studied. The test indicates that enzymatic process creates less surface damage, weight loss and improved moisture regain, dye uptake, and shear properties.